Healing the Wounds of the Soul: Trauma in Les Aubes écarlates by Leonora Miano - (:unkn) unknown (My University, 2021)
The reiterated violence exemplified in Sub-Saharan African History has been traumatic and keeps on being kindled one way or another. Léonora Miano’s novel combines theme of memory, trauma and a fictional world. In her novel, traumatic events constantly disrupt human lives by manifesting destructive repetitive actions and, consequently, by enhancing the importance of funeral rituals - those being specific to each society. This study of the novel Les Aubes écarlates aims to articulate the notion of trauma and its consequences regarding temporal, material and spiritualruptures, as well as exploring in a given fictional society its different patterns, through themes of hope and reconstruction, renewal and the dawn. A collective trauma can be overcome through the narrative process and through different practices, including healing and therapy. To that extent, female characters specifically carry a significant role in fixing damage caused by reiterated violence caught in a loop of destructive events. Women characters’ role also includes making connection between generations of humans, ancestors and newborn ones. They restore continuity and cycle of time. Hence, collective traumas lead to question the notion of time as a strict rupture, also focusing on different meanings of wounds, taking into account their material, physical or spiritual components.
Keywords: African Research